ICEER2019Aveiro: Energy and environment - challenges towards circular economy - Nídia S. Caetano; Carlos Borrego; Maria Isabel Nunes; Carlos Felgueiras (Energy Reports, 2020)
The 6th edition of the International Conference on Energy and Environment Research, ICEER 2019, took place in the end of July 2019, at the University of Aveiro, Portugal. With most of the participants coming from academia, and a few from the professional field, ICEER series is still growing and attracting increased interest. Energy production, distribution and use are fundamental for the Sustainable Development of nations, showing a clear link between the energy and environment issues. Nevertheless, these matters are frequently dealt with separately, reflecting the way they are taught, and causing strong negative impacts, and hindering progress. With a growing trend in circular economy models applied to common goods production and commercialization, ICEER 2019 had as focus theme the challenges posed by energy and environment research in a circular economy-based model. This paper presents the main achievements and conclusions of ICEER 2019 participants, through their research in the fields of energy and environment, including a brief analysis of the current requirements of Education on Sustainable Development applied to the modern technological curricula.
Keywords: 330; Circular economy; Energy; Environment; Sustainable development; Technological education